If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 192 = 3X Solving 192 = 3X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-3X' to each side of the equation. 192 + -3X = 3X + -3X Combine like terms: 3X + -3X = 0 192 + -3X = 0 Add '-192' to each side of the equation. 192 + -192 + -3X = 0 + -192 Combine like terms: 192 + -192 = 0 0 + -3X = 0 + -192 -3X = 0 + -192 Combine like terms: 0 + -192 = -192 -3X = -192 Divide each side by '-3'. X = 64 Simplifying X = 64
| -8x^2=-64 | | (1-4x)(1-3x)=6x(2x-1) | | 6,5/9=x/40 | | (5y+4w-3w-5)= | | N+4N=7N+22 | | 3.6b^3=42.5 | | 6x^2+9=4x^2+17 | | (5cd^-3/10d^5)^-1 | | (14x-28)/2x*8/7 | | 9m^2+12m+36=0 | | 6x-2=-5 | | 4(-5+1.875y)+2y=56 | | 2.3=81-3 | | (x+2)x(x+3)=0 | | 121/2=5m | | 5x^2=3x^2 | | 3x+6=-54 | | y-4=7(x+2) | | 29x=6x-8 | | 28a^9+(-8x)= | | 1/16*1/8 | | 5m=121/2 | | -4(2m-6)+9(m-3)=13-9 | | (x+5)-3((x+5)(x+5))=0 | | 9x+15=-21 | | 6y-5(y-1)+1=6 | | 6(x+8)-8x=32 | | x+6=5x-10-2x | | 4(8-3k)=3k+2 | | 6y-5(y-5)+1=6 | | 3(x^2-5)=9 | | 4x^2+5y^2=20 |